2012
DOI: 10.1186/2049-1891-3-27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of "Bioactive" amino acids leucine, glutamate, arginine and tryptophan on feed intake and mRNA expression of relative neuropeptides in broiler chicks

Abstract: Feed intake control is vital to ensuring optimal nutrition and achieving full potential for growth and development in poultry. The aim of the present study was to investigate the effects of L-leucine, L-glutamate, L-tryptophan and L-arginine on feed intake and the mRNA expression levels of hypothalamic Neuropeptide involved in feed intake regulation in broiler chicks. Leucine, glutamate, tryptophan or arginine was intra-cerebroventricularly (ICV) administrated to 4d-old broiler chicks respectively and the feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Wang et al (2012) also reported that administration of L-glutamate (1.6 μmol) decreased feed intake and increased hypothalamic CRF and MC4R mRNA expression levels. However, in those studies, the AA were injected directly in the central nervous system (ICV), and therefore, further studies to evaluate the influence of glutamine and glutamate on broiler feed intake are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al (2012) also reported that administration of L-glutamate (1.6 μmol) decreased feed intake and increased hypothalamic CRF and MC4R mRNA expression levels. However, in those studies, the AA were injected directly in the central nervous system (ICV), and therefore, further studies to evaluate the influence of glutamine and glutamate on broiler feed intake are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Although the feed efficiency in some birds, such as turkeys, is not affected by dietary supplementation with Trp, other poultry and mammals show obvious changes in feed intake after Trp supplementation (Denbow et al, 1993;Corzo et al, 2005;Wang et al, 2012). This improvement in growth performance was largely attributed to the enhanced appetite and increased feed intake induced by Trp and/or its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…##, ••, and **p < .01; *p < .05, compared with the controls of the area with the same color and is used to improve food flavor (Zeb & Rahman, 2017). Leucine is a branched-chain amino acid, known to enhance the appetite and prevent muscle injury (Wang et al, 2012). Therefore, these two amino acids may confer important biological activities to AMB.…”
Section: Discussionmentioning
confidence: 99%